2012
DOI: 10.1093/ntr/nts119
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Pregnant Women to Waterpipe and Cigarette Smoke

Abstract: Exposure of pregnant women to tobacco smoke is a public health problem in Jordan that requires immediate action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
54
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 56 publications
10
54
5
Order By: Relevance
“…Our finding of 48.9% (45.26% to 52.55%) from the 2014 Bangladesh DHS suggests prevalence of household SHS exposure has remained constant. This is similarly reflected in previous studies conducted in Jordan that have reported 50.4% of pregnant women are exposed to SHS in the home,27compared with the higher prevalence of 63.4% reported in this study. Fischer et al also found low educational attainment and low wealth to be associated with increased daily SHS exposure 26…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of 48.9% (45.26% to 52.55%) from the 2014 Bangladesh DHS suggests prevalence of household SHS exposure has remained constant. This is similarly reflected in previous studies conducted in Jordan that have reported 50.4% of pregnant women are exposed to SHS in the home,27compared with the higher prevalence of 63.4% reported in this study. Fischer et al also found low educational attainment and low wealth to be associated with increased daily SHS exposure 26…”
Section: Discussionsupporting
confidence: 90%
“…Among the smokers, 93% used cigarette smoking and 8.6% used waterpipe smoking. Another study showed that 82.4% and 32.8% of women reported exposure to passive cigarette and waterpipe smoking, respectively, in their houses and public places (8). Unfortunately, smoking in public places and even near family members in houses is not well controlled in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…Waterpipe smoking is often associated with the Eastern Mediterranean Region (EMR), where its current smoking rates are as high as 45% among some populations (Saade et al, 2009; Khabour et al, 2012b; Azab et al, 2013; Maziak et al, 2014). In the U.S., waterpipe smoking is most often seen among university students.…”
Section: Introductionmentioning
confidence: 99%